2021
DOI: 10.1001/jamaophthalmol.2021.3027
|View full text |Cite
|
Sign up to set email alerts
|

Female Editorial Authorship Trends in High-Impact Ophthalmology Journals

Abstract: IMPORTANCE Individuals with perceived experience and expertise are invited by editorial boards to provide commentary through editorials. Female representation among editorialists is not yet defined.OBJECTIVE To determine female representation as editorial authors in 3 high-impact general ophthalmology journals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…If this information is not readily available from the website and institutional profile, the editorial board member will be determined to be an ophthalmologist if they were either listed on the websites of the physician governing bodies (eg, American Board of Ophthalmology, Canadian Ophthalmological Society American Society of Retina Specialists) or had professional profiles indicating ophthalmology residency training or their position as ophthalmologists. 10 Board members not meeting any of the criteria above will be designated as non-ophthalmologists (or unknown if no information can be identified). Information on academic degrees will be obtained from the editorial board member’s most recent two publications.…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…If this information is not readily available from the website and institutional profile, the editorial board member will be determined to be an ophthalmologist if they were either listed on the websites of the physician governing bodies (eg, American Board of Ophthalmology, Canadian Ophthalmological Society American Society of Retina Specialists) or had professional profiles indicating ophthalmology residency training or their position as ophthalmologists. 10 Board members not meeting any of the criteria above will be designated as non-ophthalmologists (or unknown if no information can be identified). Information on academic degrees will be obtained from the editorial board member’s most recent two publications.…”
Section: Methods and Analysismentioning
confidence: 99%
“…The designation of ophthalmologist versus non-ophthalmologist, as well as any academic degrees including Doctor of Medicine (MD), Doctor of Philosophy (PhD) and any non-MD or PhD degrees will be collected via the journal website profiles or institutional affiliation profiles. If this information is not readily available from the website and institutional profile, the editorial board member will be determined to be an ophthalmologist if they were either listed on the websites of the physician governing bodies (eg, American Board of Ophthalmology, Canadian Ophthalmological Society American Society of Retina Specialists) or had professional profiles indicating ophthalmology residency training or their position as ophthalmologists 10. Board members not meeting any of the criteria above will be designated as non-ophthalmologists (or unknown if no information can be identified).…”
Section: Methods and Analysismentioning
confidence: 99%
“…8 Finally, this study's findings on the unequal distribution of academic degrees between the genders are consistent with the previous study by Fathy and colleagues, which suggests that when compared with men, women authoring articles in ophthalmology journals are more likely to be non-ophthalmologists and hold non-medical or non-PhD degrees. 9 Kramer and colleagues demonstrated a significant gender disparity in ophthalmic research, which may hinder career advancements for young ophthalmologists. 10 The current study further indicates that this gap may persist throughout an ophthalmologist's career even in highly visible positions as journal editorial board members.…”
Section: Open Accessmentioning
confidence: 99%
“…The Association of American Medical Colleges (AAMC) reported that the percentage of women in the physician workforce has increased from 28.3% in 2007 to 36.3% in 2019 . This increase in representation is reflected in the field of ophthalmology with a female representation of 14% to 17% in the early 2000s increasing to 25% in 2020 . Despite this increase, significant disparities still exist in academic rank, productivity, faculty retention and promotion, and compensation .…”
Section: Introductionmentioning
confidence: 99%